2020
DOI: 10.1590/0037-8682-0692-2020
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke related to HIV and SARS-COV-2 co-infection: a case report

Abstract: A 56-year-old male with human immunodeficiency virus required hospitalization due to the onset of both dyspnea and asthenia. A computed tomography of the chest exam showed the radiological pattern of coronavirus SARS-CoV-2 pulmonary involvement. Based on immunochromatographic analysis, the patient evolved as a reagent for immunoglobulin M (IgM) and immunoglobulin G (IgG) anti-SARS-CoV-2 antibodies. The individual developed complete hemiparesis with a predominance in the right arm and conduction aphasia. T1weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
0
6
0
6
Order By: Relevance
“…The remaining 71 articles (127 patients) that satisfied the criteria mentioned above were included in this review. In this review, 80 cases of patients developed IS during COVID-19 infection (Aasfara et al 2021 ; Abdulkadir et al 2020 ; Agarwal et al 2020 ; Al-Mufti et al 2021 ; Al Saiegh et al 2020 ; Appavu et al 2021 ; Ashraf and Sajed 2020 ; Avula et al 2020 ; Bessa et al 2020 ; Bigliardi et al 2020 ; Burkert and Patil 2020 ; Co et al 2020 ; Dakay et al 2020a , b ; de Almeida Lima et al 2020 ; de Lorenzo Alvarez et al 2021 ; Deliwala et al 2020 ; Dumitrascu et al 2020 ; Efendizade et al 2020 ; El Nahas et al 2020 ; Elshereye and Erdinc 2020 ; Eskandarani et al 2021 ; Fu et al 2021 ; Garg et al, 2020 ; Gemcioglu et al 2020 ; Goette et al 2020 ; Goldberg et al 2020 ; Guillan et al 2020 ; Iqbal et al 2021 ; Kwon et al 2020 ; Mahboob et al 2020 ; Mansour et al 2020 ; Mirzaee et al 2020 ; Morassi et al 2020 ; Mowla et al 2020 ; Patel et al 2020a , b ; Patel et al 2020a , b ; Prasad et al 2021 ; Priftis et al 2020 ; Rajdev et al 2020 ; Rascón-Ramírez et al 2020 ; Roy et al 2021 ; Valderrama et al 2020 ; Viguier et al 2020 ; Zhai et al 2020 ), 32 cases developed intracranial hemorrhage (Ahmad et al 2021 ; Al-Mufti et al 2021 ; Al Saiegh et al 2020 ; Carroll and Lewis 2021 ; Cezar-Junior et al 2020 ; Dakay et al 2020a , b ; Dakay et al 2020a , ...…”
Section: Resultsmentioning
confidence: 94%
“…The remaining 71 articles (127 patients) that satisfied the criteria mentioned above were included in this review. In this review, 80 cases of patients developed IS during COVID-19 infection (Aasfara et al 2021 ; Abdulkadir et al 2020 ; Agarwal et al 2020 ; Al-Mufti et al 2021 ; Al Saiegh et al 2020 ; Appavu et al 2021 ; Ashraf and Sajed 2020 ; Avula et al 2020 ; Bessa et al 2020 ; Bigliardi et al 2020 ; Burkert and Patil 2020 ; Co et al 2020 ; Dakay et al 2020a , b ; de Almeida Lima et al 2020 ; de Lorenzo Alvarez et al 2021 ; Deliwala et al 2020 ; Dumitrascu et al 2020 ; Efendizade et al 2020 ; El Nahas et al 2020 ; Elshereye and Erdinc 2020 ; Eskandarani et al 2021 ; Fu et al 2021 ; Garg et al, 2020 ; Gemcioglu et al 2020 ; Goette et al 2020 ; Goldberg et al 2020 ; Guillan et al 2020 ; Iqbal et al 2021 ; Kwon et al 2020 ; Mahboob et al 2020 ; Mansour et al 2020 ; Mirzaee et al 2020 ; Morassi et al 2020 ; Mowla et al 2020 ; Patel et al 2020a , b ; Patel et al 2020a , b ; Prasad et al 2021 ; Priftis et al 2020 ; Rajdev et al 2020 ; Rascón-Ramírez et al 2020 ; Roy et al 2021 ; Valderrama et al 2020 ; Viguier et al 2020 ; Zhai et al 2020 ), 32 cases developed intracranial hemorrhage (Ahmad et al 2021 ; Al-Mufti et al 2021 ; Al Saiegh et al 2020 ; Carroll and Lewis 2021 ; Cezar-Junior et al 2020 ; Dakay et al 2020a , b ; Dakay et al 2020a , ...…”
Section: Resultsmentioning
confidence: 94%
“…First, we showed that characteristic aphasia could occur as a focal neurological deficit associated with SARS-CoV-2-related encephalopathy using SPECT. Although aphasia associated with SARS-CoV-2-related encephalopathy [ 2 , 3 ] or secondary ischemic stroke has been reported [ 4 , 5 ], focal lesions on imaging have not been demonstrated (Supplemental Fig 1 ). Additionally, MR angiography showed no stenosis or occlusion (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological manifestations of coronavirus disease 2019 (COVID-19) are increasingly recognized and include encephalopathy, although direct infection of the brain by SARS-CoV-2 remains controversial [ 1 ]. Aphasia has been reported as a symptom of SARS-CoV-2-related encephalopathy [ 2 , 3 ] or SARS-CoV-2-related ischemic stroke [ 4 , 5 ]. Therefore, discrimination between encephalopathy and stroke is very important to treat aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the traditional risk factors, HIV is associated with other factors that increase the risk of stroke, including immunosuppression and high viremia, as in our patient. The etiology of stroke in people living with HIV is multifactorial, including Atherosclerosis of the large arteries, small vessel disease, cardio embolism, central nervous system (CNS) infections, coagulation disorders, and non-atherosclerotic vasculopathy, yet the triggering mechanism for stroke remains unclear (13). A possible explanation of the presentation at this age is that the myocardial infarction was directly related to HIV chronic in ammation and immune activation independent of other risk factors (6).…”
Section: Discussionmentioning
confidence: 99%